استخدام الطرائق العشوائيَّة شبه المتدرجة لحل بعض مسائل الأمثليات العشوائيَّة غير المحدّبة وغير الملساء. (Latakia University Journal -Basic Sciences Series, 2014)
الغاية من البحث هي دراسة وتحليل بعض الطرائق العشوائيَّة شبه المتدرّجة وإمكانية تطبيقها لإيجاد الحل الأمثل لمسائل أمثليّة تخضع لمؤثّرات عشوائيّة وظروف تتحكّم فيها الصدفة. وقد تم إثبات تقارب بعض هذه الطرق الرياضيّة وفعاليتها من أجل بعض المسائل العشوائيَّة غير المحدّبة وغير الملساء والمزوّدة بدالة هدفية وقيود محدّدة وحيث اتخذ مجمّع الطاقة الشمسية كمثال على ذلك.   The purpose of research is the study and analysis of some of the stochastic semi-gradient methods and their applicability to find the optimal solution for the issues of optimization are subject to the effects Random and conditions are controlled by chance, as we proved the convergence of some of these mathematical methods and their effectiveness for some of the issues of stochastic non-convex and equipped objective function and specific constraints and where taken energy complex solar as an example.